2021
DOI: 10.1155/2021/6620913
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti‐Inflammatory Profiles of Spent Coffee Ground Extracts for the Treatment of Neurodegeneration

Abstract: Spent coffee grounds (SCGs), waste products of coffee beverage production, are rich in organic compounds such as phenols. Different studies have demonstrated phenol beneficial effects in counteracting neurodegenerative diseases. These diseases are associated with oxidative stress and neuroinflammation, which initiates the degeneration of neurons by overactivating microglia. Unfortunately, to date, there are no pharmacological therapies to treat these pathologies. The aim of this study was to evaluate the pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…However, our results did not show anti-inflammatory activity of SCG from caffeinated and decaffeinated coffee extracts on the RAW 264.7 cell line. A recent publication reported that the SCG water extracts are more effective than extracts obtained with solvents [ 59 ]. Nevertheless, when considering the antifungal activity of the extracts obtained in this study in fungi agents of human skin infections together with the absence of cytotoxicity on a non-tumoral cell line, it can be anticipated as a possible utilization in the therapy of dermatomycosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results did not show anti-inflammatory activity of SCG from caffeinated and decaffeinated coffee extracts on the RAW 264.7 cell line. A recent publication reported that the SCG water extracts are more effective than extracts obtained with solvents [ 59 ]. Nevertheless, when considering the antifungal activity of the extracts obtained in this study in fungi agents of human skin infections together with the absence of cytotoxicity on a non-tumoral cell line, it can be anticipated as a possible utilization in the therapy of dermatomycosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it promoted neuronal differentiation by inducing the expression of neuronal markers from the MAPK signaling pathway, which modulated the growth and stabilization of microtubules in neurites [ 48 ]. Angeloni et al (2021) reported that coffee by-product extract was able to reduce the activity of pro-inflammatory enzymes, such as iNOS and COX-2, and the levels of different pro-inflammatory mediators by reducing NF-kB proteins to basal levels [ 89 ]. In fact, these coffee extracts showed catechin content, in accordance with LSE.…”
Section: Phenolic Compounds From Fruit and Vegetable By-products: Neu...mentioning
confidence: 99%
“… Main mechanisms through which plant extracts and their phenolic compounds exert their neuroprotective effects, as well as key cell processes involved. Finally, several references in which this information is demonstrated [ 30 , 34 , 41 , 48 , 57 , 58 , 75 , 79 , 80 , 81 , 85 , 86 , 87 , 88 , 89 , 92 , 93 , 95 , 102 , 108 , 110 , 115 , 123 , 130 , 131 ]. …”
Section: Figurementioning
confidence: 99%
“…The data showed that caffeine and chlorogenic acids were the most abundant compounds in all samples followed by phenolic acids. Neuroprotective activity of silverskin and spent coffee extracts against H 2 O 2 -induced damage was evaluated for the first time suggesting for methanol and ethanol/water (70:30) extracts a potential role as protective agents against neurodegeneration due to their ability to counteract oxidative stress and maintain cell viability [ 31 , 32 ].…”
Section: Summary Of Conference Presentationsmentioning
confidence: 99%